2013
DOI: 10.1161/circimaging.113.000185
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of Biopolymer-Delivered Circulating Angiogenic Cells in a Swine Model of Hibernating Myocardium

Abstract: M yocardial hibernation is a common clinical condition affecting patients with advanced coronary artery disease, 1 for whom cell-based therapies are targeted. In hibernation, repetitive episodes of ischemia and reperfusion lead to metabolic and functional changes in cardiomyocytes, ultimately impairing left ventricular (LV) function. Current therapies such as coronary artery bypass grafting or percutaneous coronary intervention are well established but not suitable for all patients; in previous clinical resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…This may explain the greater improvement in WT% and SRS% with PQS. Consistent with previous studies [18,29], myocyte nuclear density was increased by PQS. Treatment with PQS attenuated the cellular hypertrophy, indicating that PQS improve oxygen transport across the sarcolemma in the ischemic myocardium [30].…”
supporting
confidence: 93%
See 1 more Smart Citation
“…This may explain the greater improvement in WT% and SRS% with PQS. Consistent with previous studies [18,29], myocyte nuclear density was increased by PQS. Treatment with PQS attenuated the cellular hypertrophy, indicating that PQS improve oxygen transport across the sarcolemma in the ischemic myocardium [30].…”
supporting
confidence: 93%
“…Nuclei were counter-stained with DAPI. To determine arteriole density, 6 random fields per slide were captured at 200× magnification using a fluorescent microscope [18]. Blood vessels with a diameter <100 μm were counted by two independent examiners.…”
Section: Arteriole Densitymentioning
confidence: 99%
“…The common modalities used to measure these parameters included: echocardiography, MRI, and immunohistochemistry. Out of the 21 studies, Giordano et al, 2013 [ 19 ], Yamamoto et al, 2001 [ 20 ], Zhou et al, 2012 [ 10 ], Liu et al, 2006 [ 11 ], and Takehara et al, 2008 [ 29 ] did not measure the direct effect of treatment on LV remodeling. The remaining 16 studies that looked into LV remodeling reported either attenuated or equivocal LV remodeling.…”
Section: Resultsmentioning
confidence: 99%
“…The degree of angiogenesis was mainly quantified using blood vessel density via immunohistochemistry staining. Out of the 21 studies, only 11 [ 10 , 11 , 14 , 19 , 21 , 23 , 25 , 26 , 27 , 28 , 30 ] measured blood vessel density; each of the 11 studies reported an improved effect, implying that hydrogel treatment can have a positive effect on angiogenesis post-MI. Zhou et al [ 10 ] particularly focuses on the density of specific blood vessels—namely arterioles, small vessels, and larger arterioles—all of which show an increase in density.…”
Section: Resultsmentioning
confidence: 99%
“…4 This surgical intervention is well established and leads to a classic model of hibernating myocardium. 4,11,12,23 Teramato and colleagues 3 previously reported a swine model of HF induced by permanent ligation on the distal portion of the LAD, followed by proximal placement an ameroid constrictor to occlude the proximal portion. This study was able to demonstrate a high survival rate out to 4-month post-surgery (75%), and characterized LV remodeling in the setting of reduced EF, and increased end-diastolic and end-systolic volumes with initial development of fibrosis in the remote regions.…”
Section: See Related Article Pp 655-665mentioning
confidence: 99%